The Role of Leadership and Work Loyalty in Improving Work Assessment at the North Sumatra Provincial Cooperatives and SMEs Office UPT. PLUT - Evi Beatric Dewi Zebua; M. Chaerul Rizky; Adinda Desi Sapuri; Kurniawan Syahputra; Halimah Tusakdiyah Nasution (Transpublika Publisher, 2025)
Employee performance assessment is a fundamental aspect in human resource management that determines the effectiveness of government organizations. North Sumatra Province Cooperatives and SMEs Office UPT. PLUT as an agency that plays a role in community economic empowerment faces challenges in optimizing employee performance. Effective leadership and high job loyalty are suspected to be determinant factors in improving employee work assessment. This paper seeks to identify the influence of leadership and occupational allegiance in augmenting performance evaluations within the UPT PLUT Office of Cooperatives and SMEs, North Sumatra Province, while simultaneously delineating the causal interplay among leadership, work loyalty, and employee performance metrics. The investigation adopts a quantitative methodological framework, encompassing the entire personnel population of 57 individuals at the UPT PLUT Office of Cooperatives and SMEs, North Sumatra Province. The sampling framework employed a census (saturated sampling) technique, ensuring comprehensive representativeness. The instrumentation apparatus consisted of a Likert-scaled questionnaire, meticulously constructed to gauge perceptual tendencies across relevant dimensions. Data processing and inferential analytics were executed through multiple regression modeling utilizing SPSS software version 29. Empirical revelations elucidate that leadership exerts a favorable and statistically consequential impact upon employee performance indices. Meanwhile, occupational fealty was substantiated to impart a constructive and substantively meaningful influence on performance outcomes. Collectively, leadership and professional dedication were observed to synergistically contribute a salient effect on employee efficacy, with an R² coefficient of 0.311 (31.1%), signifying that these two determinants collectively accounted for 72.3% of the observed variance in performance appraisals.